Analisis Pendapatan Kerajinan Rotan Di Desa Tumbang Habangoi Kecamatan Petak Malai, Kabupaten Katingan: Analysis Income of Rattan Handicrafts in Tumbang Habangoi Village Petak Malai Subdistrict, Katingan Regency - Nursiah, Nursiah; Birawa, Cakra; Sudomo, Muhammad Fadhil Amiruddin; Hartatie, Sri (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
This study aims to describe the techniques of rattan processing and the production process of rattan handicrafts, analyze the income of rattan artisans, and identify the challenges faced by artisans in Tumbang Habangoi Village. The research employed a saturated sampling method (census) and collected data through observation, interviews, and questionnaires. Data were analyzed using revenue and income analysis, as well as qualitative descriptive methods. The findings indicate that the rattan processing and crafting stages typically involve soaking the rattan, drying the stems, cleaning the stems (locally known as maruntih and mangalingking), processing, cutting, and splitting the rattan stems and strands, skinning, thinning, and weaving. The resulting woven products include mats, bags, lanjung (traditional backpacks), baskets, tangok, embung, tampi, pot coasters, and bubu (fish traps). The average annual production cost is IDR 449,875, with an average annual revenue of IDR 1,522,500 and an average annual income of IDR 1,246,750. The primary challenges identified include limited market access and a lack of product innovation, which hinder the development of rattan handicrafts in the community.